Effect of ionic liquid inclusion and amino-functionalized SAPO-34 on the performance of mixed matrix membranes for CO2/CH4 separation - Nasir, R. (Elsevier Ltd, 2018)
Surface voids and filler agglomeration affect the membrane's structure and gas separation which limits the use of mixed matrix membranes (MMM) for carbon dioxide (CO2) separation in industry. Therefore, synthesis of MMM with ionic liquid and modified inorganic fillers had improved performance and morphologies. In this regards the filler surface (SAPO-34) was modified by introducing organic amino cation, namely ethylenediamine (EDA) and hexylamine (HA). Four (04) mixed matrix membranes were synthesized by the incorporation of un-modified and modified filler along with ionic liquid (IL) in polyethersulfone (PES) matrix. The effects of IL addition and filler functionalization on morphology, thermal and mechanical stability were investigated; while pure gas permeation test using carbon dioxide (CO2) and methane (CH4) was carried out at 4bar pressure to analyze the membrane gas transport properties. Characterization showed that surface voids and hard agglomerations disappeared by the addition of modified SAPO-34 and ionic liquid emimTf2N. Moreover, membranes were thermally and mechanically stable after the addition of IL and modified SAPO-34. Synergetic effect of IL and modified filler exhibited excellent CO2/CH4 selectivity (37.23) for PES+ IL+ modified SAPO-34+ HA MMM. Â© 2018 Elsevier Ltd. All rights reserved.